2019
DOI: 10.1038/s41598-018-38094-1
|View full text |Cite
|
Sign up to set email alerts
|

Microbes Producing L-Asparaginase free of Glutaminase and Urease isolated from Extreme Locations of Antarctic Soil and Moss

Abstract: L-Asparaginase (L-asparagine aminohydrolase, E.C. 3.5.1.1) has been proven to be competent in treating Acute Lymphoblastic Leukaemia (ALL), which is widely observed in paediatric and adult groups. Currently, clinical L-Asparaginase formulations are derived from bacterial sources such as Escherichia coli and Erwinia chrysanthemi. These formulations when administered to ALL patients lead to several immunological and hypersensitive reactions. Hence, additional purification steps are required to remove toxicity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 40 publications
2
46
0
3
Order By: Relevance
“…Acute lymphoblastic leukemia (ALL) is a blood cancer commonly ripens in children. Treatment with L-asparaginase enzyme was shown to achieve complete remission in ALL (Ashok et al, 2019, Brumano et al,2018) which was shown to be mediated by hydrolysis of aspartic acid-ammonia in the blood (Pike et al,2019). When L-asparaginase is administered to ALL patients, it depletes asparagine levels in the blood.…”
Section: Introductionmentioning
confidence: 99%
“…Acute lymphoblastic leukemia (ALL) is a blood cancer commonly ripens in children. Treatment with L-asparaginase enzyme was shown to achieve complete remission in ALL (Ashok et al, 2019, Brumano et al,2018) which was shown to be mediated by hydrolysis of aspartic acid-ammonia in the blood (Pike et al,2019). When L-asparaginase is administered to ALL patients, it depletes asparagine levels in the blood.…”
Section: Introductionmentioning
confidence: 99%
“…The isolates were grown on media containing specific substrates for the respective enzymes as performed in the screening experiment described above and diameter of the zones of clearance and that of the colonies were measured. Amount of the enzyme produced was then calculated, and expressed as enzyme intensity (EI) where EI = (colony diameter + halo zone diameter)/colony diameter ( Aleem et al, 2018 ; Ashok et al, 2019 ). Each experiment was performed in triplicate and averaged.…”
Section: Methodsmentioning
confidence: 99%
“…They demonstrated to produce L-Asparaginase free of glutaminase and urease, proven to be competent in treating acute lymphoblastic leukaemia which is most common type of childhood cancer. Among the strains screened, T. asahii IBBLA1 exhibited the highest enzyme activity [43].…”
Section: Enzymesmentioning
confidence: 99%